The Age of Analogy : Science and Literature between the Darwins - Griffiths, Devin, 1978- (Book collections on Project MUSE., 2016)
"Drawing on a wide range of archival evidence and contemporary models of scientific and literary networks, The Age of Analogy explores the critical role analogies play within historical and scientific thinking. Griffiths also presents readers with a new theory of analogy that emphasizes language's power to foster insight into nature and human society. The first comparative treatment of the Darwins' theories of history and their profound contribution to the study of both natural and human systems, this book will fascinate students and scholars of nineteenth-century British literature and the history of science"--Provided by publisher.